Appropriate feeding method with automatic feeder for Giant freshwater prawn culture (Macrobrachium rosenbergii de Man) - ธานี, สุภัชญา; Sangduan, Wirongrong (Science Technology and Innovation Journal, 2023)
A study of feed centrifugation patterns suitable for nursery and culture rearing To determine the centrifuge pattern by auto-feed centrifuge in raising young and fattening Giant freshwater prawn (Macrobrachium rosenbergii de Man). As a guideline for determining the centrifuge of feed suitable for growth in weight, length, and survival rate of Giant freshwater prawn, in phase 1, 4 centrifuge patterns were tested and the results were obtained from feed centrifugation 2. The best model was tested in Phase 2 in 2x4x1 m. cages and 50 shrimps were released per cage. Results in Phase 1 and Phase 2 showed that feed centrifugation at the edge of the pond Both stages of Giant freshwater prawns have the best growth. followed by throwing food into the middle of the pond When considering the growth rate of Giant freshwater prawns in the second stage, it was found that the mean weight growth of young lobsters was statistically different (p<0.05). The statistical significance (p < 0.01). In the fattening Giant freshwater prawn, it was found that the growth effect was different from the young Giant freshwater prawn as follows: the mean weight growth of the lobster was statistically different. The growth in length was not significantly different (p>0.05). The survival rate had the same effect in both phases. Significantly (p<0.01), the proper form of centrifugation of lobster feed should be that the automatic centrifuge should be centrifuged to the edge of the pond to affect feed access. growth and the best survival rate.